Factors affecting exclusive breastfeeding practices among working-class women in Osun State, Nigeria - Olariike O. Kayode; Ayobami S. Oyedeji; Quadri K. Alabi (AOSIS, 2023)
Breastfeeding has been accepted as the most vital intervention for reducing infant mortality and ensuring optimal growth and development of children. However, studies on the factors affecting exclusive breastfeeding, especially, among working-class women are sparse. This study determined the factors affecting exclusive breastfeeding among working-class women in Osun state. Multistage sampling was used to select a total of 316 respondents for this cross-sectional study and a pretested, interviewer-administered questionnaire was used to elicit information. More than half (57.6%) of the respondents were between the ages of 26-35 years. Ninety-eight percent (98.1%) of the respondents had good knowledge of exclusive breastfeeding (EBF). Sixty-six percent (66.8%) had good exclusive breastfeeding practices. The study showed that there was a significant relationship between knowledge and practices of exclusive breastfeeding among the respondents (P0.05). Identified factors affecting exclusive breastfeeding among the respondents are: duration of maternity leave, availability of crèche near the place of work, breastfeeding break at work, husband and family support, health conditions that could hinder EBF, and engagement in other activities with work. Breastfeeding breaks at work (AOR=4.717; P=0.000), husband and family support (AOR=2.944; P=0.000), and one-month maternal leave (P=0.000) were factors significantly associated with EBF practices. We conclude that good knowledge and good practices of exclusive breastfeeding were found among the study group. Improved policies around maternity leave and the provision of breastfeeding friendly work environment are needed to increase exclusive breastfeeding practices. Husbands and family members should be educated on the need to provide support to breastfeeding mothers.